The Religion Teachers Performance at Aliya Madrasa after their Completing Training Program in Province of West Nusa Tenggara - AM Wibowo (Analisa: Journal of Social Science and Religion, 2013)
This research aims to evaluated the religions teachers performance at Aliya Madrasa after attending training functional programs which managed by Balai Diklat Keagamaan on province of West Nusa Tenggara. This research important to do to seeing the change of religion teacher performance on Aliya Madrasa whether increase or decrease after attending training functional program. By using analysis of context, input, process, product (CIPP) this study had 4 findings, there are: (1) In pedagogic competency, personality, social and professional, the performances of religion teachers in Aliya Madrasa after attending training functional programs were include into fairly category. However in competition achivement the religion teacher is under expectation. (2) Performance of the religion teacher in Aliya Madrasa after attending   training functional programs give positive impact on students achievement. 3) The facilities of school like management, regulation and commitment of principal of Aliya Madrasa give positive impact to teacher performance, whereas support facilities in Aliya Madrasa is not support the increasing of religion teacher performance. (4) The Religion teachers performance after participated training functional programs gave positive impact to other teachers.